Population-specific causal disease effect sizes in functionally important regions impacted by selection - Huwenbo Shi (Nature Portfolio, 2021)
Trans-ethnic genetic correlation is significantly less than 1 for many diseases. Here, the authors stratify this correlation by genomic annotations, finding that loci whose causal disease effect sizes differ between ethnicities are likely impacted by selection, particularly positive selection.